EVALUASI PEMBERIAN IZIN USAHA PERTAMBANGAN (IUP) DI KABUPATEN SUMBA TENGAH, NTT - Kresna Umbu Haingu; Susilo Utomo; Sulityowati . (Journal of Politic and Government Studies, 2015)
Development policy provided through the Mining Permit (IUP) have a major impact on people's lives. Impact question is conflict that left three people villagers Praikaroku Jangga be suspect. Given the policy violates the rules of the aa in Law 4 of 2009 on Mineral and Coal Mining. In accordance with Law No. 4 of 2009 on Mineral and Coal which has regulated the Mining Business Permit (IUP) in a region must understand the applicable regulations. In the case of mining in Central Sumba District, the local government in this case the regent less true examine the existing provisions so that the measures taken in the Regent give conflicting recommendations. In this study, researchers used a qualitative research method, the type of research that is used is the type of descriptive with the aim to portray the factual situation, systematic and accurate. The study was conducted to collect data that is accurate and extensive search for information through interviews, documentation, library research and field observations. The results showed that the government violated the provisions of Law no. 4 in 2009. The issue of kewajban IUP holder, about the mining area, IUP discharge requirements, concerning the suspension of mining. It is not understood very well by the local government district of Central Sumba. The impact of the policy pursued by the government, namely the conflict in the mining area which resulted in tools drill on fire company and the community were arrested. In anticipation of the same conflict, the government should understand and learn well the existing regulations as stipulated2by the Act so as not give rise to misunderstanding and conflict led to the community. The government also needs to conduct a review of the policy given by recommendation in 2007. Keywords: Local government, Mining License, Policy